2011
DOI: 10.1002/ejoc.201100178
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5‐(Fluorophenyl)tocopherols as Novel Dioxin Receptor Antagonists

Abstract: γ‐Tocopherol, a component of the essential nutrient mixture commonly designated as vitamin E, was chemically combined with differently substituted monofluoro‐ and difluorophenyl moieties to produce potential antagonists for the human aryl hydrocarbon receptor (AhR). 5‐Iodo‐γ‐tocopherol was a very reliable starting material for the Pd‐catalyzed reaction with (fluorophenyl)boronic acids (Suzuki coupling). The ortho‐ and meta‐fluoro‐substituted derivatives showed conformational isomerism due to restricted rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…In this study, we found that TCDD exposure caused osteoblast cytotoxicity and oxidative stress, whereas xanthohumol mitigated these effects. Kloser et al (2011) demonstrated that antioxidants such as tocopherol are antagonistic to TCDD and have been found to decrease the concentration of nitrogen peroxide and decrease damage to single-stranded DNA (Alsharif & Hassoun, 2004). Several studies have demonstrated that ROS produced during oxidative stress initiated signaling cascades leading to cytotoxicity and autophagy (Kim et al, 2007;Scherz-Shouval et al, 2007).…”
Section: Opg (Fold)mentioning
confidence: 99%
“…In this study, we found that TCDD exposure caused osteoblast cytotoxicity and oxidative stress, whereas xanthohumol mitigated these effects. Kloser et al (2011) demonstrated that antioxidants such as tocopherol are antagonistic to TCDD and have been found to decrease the concentration of nitrogen peroxide and decrease damage to single-stranded DNA (Alsharif & Hassoun, 2004). Several studies have demonstrated that ROS produced during oxidative stress initiated signaling cascades leading to cytotoxicity and autophagy (Kim et al, 2007;Scherz-Shouval et al, 2007).…”
Section: Opg (Fold)mentioning
confidence: 99%
“…The improving effect obtained after a long-term use of TCP in both tests can be justified by a protective role of this vitamin on the phospholipids of cell membranes, mitochondrial membranes, as well as reduced activity of free radicals and nitric oxide, and lower level of TNF concentration, which is also confirmed by studies of other authors. [50][51][52] Administration of ASA in ASA (F) group also resulted in shorter response times, which confirms the positive effect of ASA on neurotransmission. Similar results are presented in the studies by Gong et al, Wang and Lu et al 40,53,54 This study confirms that ASA is an antagonist of the glycine receptor and it reduces the inhibitory effect of GABA, releases glutamate from presynaptic terminals, resulting in the facilitation effect, which induces the hyperreactivity.…”
Section: Discussionmentioning
confidence: 73%
“…36,47,63 The anti-inammatory properties of ASA constitute a valuable addition to the antagonistic effect of this drug on the aryl hydrocarbon receptor. 36,38 It is worth mentioning that in the literature there is only a small amount of data concerning the inuence of TCDD on the content of magnesium, zinc and iron in bones. 64 It was shown that the administration of TCDD contributed to changes in the content of magnesium in the cytosol of liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in recent studies that two well-known substances, a-tocopherol and acetylsalicylic acid (ASA), have properties that can reduce the effects of dioxins poisoning. 3,31,36,38,39 Nowadays, monitoring the constant exposure of humans and animals to dioxins and their inuence on bone mineralization is essential for the prevention of dioxin intoxication and the development of effective pharmacological treatment methods…”
Section: Introductionmentioning
confidence: 99%